Sealing ability of different bioceramic materials used to repair furcal perforation: an in-vitro spectrophotometer analysis - Shrestha, Kriti; Shubham, Snigdha; Gautam, Vanita; Tripathi, Rupam; Arora, Chetna; Ahmed, Sageer (Journal of Chitwan Medical College, 2022)
Background: The choice of sealing material is a crucial factor that influences the outcome of endodontic treatment. Several materials such as IRM, composite, RMGIC were the most commonly used perforation repair materials. However, none of these materials were able to re-establish the normal architecture predictably in perforated furcations. Contemporary Bioceramic materials have been presumed to have promising result. The aim of this study was to compare sealing ability of different Bioceramic materials used to repair furcal perforation. Methods: Sample size of 60 extracted maxillary and mandibular molars were taken. Access opening done and furcal perforation made with #4 carbide bur. The teeth were divided into two control groups i) Negative control with no furcal perforation and ii) Positive control where furcal perforation was sealed with GIC and four experimental groups where furcal perforation were repaired with i) ProRoot MTA, ii) MTA Angelus, iii) MTA plus and iv) Biodentine respectively, each group containing 10 teeth. Microleakage was evaluated by GLM using UV Spectrophotometer for duration of 20 days. Results: The least microleakage was observed in Biodentine followed by MTA Plus, MTA Angelus and ProRoot MTA till 11th day whereas on 15th and 20th day the least microleakage was observed in MTA Plus followed by Biodentine, MTA Angelus and ProRoot MTA. Conclusions: There is no significant difference between mean microleakage of MTA Plus and Biodentine emphasizing the fact that both materials are comparable in terms of its sealing ability.